2021
DOI: 10.1186/s12873-021-00501-8
|View full text |Cite
|
Sign up to set email alerts
|

A machine learning model to predict critical care outcomes in patient with chest pain visiting the emergency department

Abstract: Background Currently, the risk stratification of critically ill patient with chest pain is a challenge. We aimed to use machine learning approach to predict the critical care outcomes in patients with chest pain, and simultaneously compare its performance with HEART, GRACE, and TIMI scores. Methods This was a retrospective, case-control study in patients with acute non-traumatic chest pain who presented to the emergency department (ED) between Janu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 32 publications
0
13
0
Order By: Relevance
“…Brajer et al suggested a machine-learning model fact sheet reporting for end-users 18 . Visualization-based efforts such as population, patient, and temporal level feature importance, or nomograms, could be adopted [19][20][21][22]…”
Section: Discussionmentioning
confidence: 99%
“…Brajer et al suggested a machine-learning model fact sheet reporting for end-users 18 . Visualization-based efforts such as population, patient, and temporal level feature importance, or nomograms, could be adopted [19][20][21][22]…”
Section: Discussionmentioning
confidence: 99%
“…Brajer et al suggested a machine-learning model fact sheet reporting for end-users 18 . Visualization-based efforts such as population, patient, and temporal level feature importance, or nomograms, could be adopted [19][20][21][22] . Like the Transparent reporting of a multivariable prediction model for individual prognosis or diagnosis (TRIPOD) or The Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) guidelines for reporting machine learning results 23,24 , there should be a guideline for the standardization of user interfaces (UIs) and a format for clinical decision support for end-users, including clinicians and patients.…”
Section: Discussionmentioning
confidence: 99%
“…In the field of healthcare, artificial intelligence (AI) has a wide range of applications, including imaging and diagnostics, lifestyle management and supervision, nursing, emergency and hospital management, drug mining, virtual assistants, wearables, and more ( 13 , 14 ). AI in the healthcare industry can tremendously improve the efficiency of clinical work and reduce the shortage of medical resources.…”
Section: Introductionmentioning
confidence: 99%